PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA BERBASIS DISCOVERY LEARNING MEMFASILITASI KPMM BARISAN DAN DERET PESERTA DIDIK SMA/MA - Fazlur Rahman; Armis Armis; Putri Yuanita (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2023)
This research produces the learning devices based  discovery learning on subject of sequences and series number which can facilitate the mathematical problem solving abilities of senior high school students who have valid and practical criteria. This research is a development study using the ADDIE development model which consists of analysis, design, development, implementation, and evaluation stages. Based on the validation by three experts, is obtained information that the learning devices are very valid. Based on the field test on students of senior high school students in Simpang Kanan in Riau Province, was obtained information that students’worksheets  were very practical applications. Therefore, the learning  devices have developed have qualified criteria of valid and practical applications to facilitate students' mathematical problem solving abilities.